Observational research on alcohol use and chronic disease outcome: New approaches to counter biases - Liang, Wenbin; Chikritzhs, Tanya (Hindawi Publishing Corporation, 2013)
Background. The frequently reported protective effects of moderate alcohol consumption in observational studies may be due to unadjusted bias. Aim. To examine two new approaches that account for unknown confounding factors and allow the application of intention-to-treat analysis. Method. This study used data from the 2008, 2009, and 2010 National Health Interview Surveys conducted in the United States. Unknown confounding effects were estimated through the association between parental alcohol use and health outcomes for children, because the presence of hypothetical physiological effects of alcohol can be ruled out for this association. In order to apply intention-to-treat analysis, previous alcohol use of former drinkers was obtained by using multiple imputations. Estimates with new adjustment approaches were compared with the traditional approach. Results. The traditional analytical approach; appears to be consistent with findings from previous observational studies; when two further adjustment approaches were used, the “protective” effects of moderate drinking almost disappeared. Conclusion. Use of a proxy outcome to estimate and control residual confounding effects of alcohol use and application of the intention-to-treat principle could provide a more realistic estimation of the true effects of alcohol use on health outcomes in observational epidemiological studies.